Control interno administrativo - financiero y su incidencia en la rentabilidad en la asociación de productores "Maná Agro" ubicada en el cantón La Maná provincia de Cotopaxi año 2021 - Guanín Masapanta, Johanna Elizabeth (2022)
The present research work contemplated as a general objective the execution of an internal administrative-financial control of La Maná Agro Association and the incidence in its profitability. Consequently, the type of investigation used was non-experimental, descriptive, and bibliographical and based on the mixed method. The authors appealed to quantitative and qualitative methods for collecting numerical and analytical data, whose population were the partners, collaborators, and leaders of this association, but it was not possible to use a sample because the population was quite limited. In due course, the employment of an internal control questionnaire allowed them to know the company's situation about its control and management considering the administrative and financial condition. Furthermore, the execution of profitability indicators to the financial statements lets them analyze its profitability and identify the current company situation. So, the researchers can prepare a beneficial proposal for the development and welfare of the company. Thanks to the questionnaire, the authors determined that the company has not effectuated its internal control and presents administrative shortcomings and a lack of training of administrative personnel and leaders. For this reason, this research proposal offers a procedure’s manual elaboration. When analyzing the financial statements with the profitability indicators, it was possible to establish that the company is stable, but the product cost must have a reasonable price to obtain more profit in its sales without quality loss.